Perception of the apprentices regarding Kinesthetic Didactics in the FPI, face-to-face at the Center for Services Center of SENA Risaralda Region - Arenas Jaramillo, Adriana María
This research was conducted to know the perception of the apprentices of the SENA Trade and Services Center, Risaralda Regional, on the use of kinesthetic-type didactic activities in the pedagogical sessions oriented in the training environments. For this study, the exploratory qualitative research approach was used, which aims at establishing norms of conduct and concrete behaviors based on the information obtained. It was contextualized with all the training programs offered at the Training Center during the second and third quarters of 2019.